Degradation of hybrid material l, d-PLA : 5CB : SWCN under the influence of neutral, acidic, and alkaline environments. Issue 6 (26th January 2023) - Fryń, Patryk; Lalik, Sebastian; Bogdanowicz, Krzysztof A.; Górska, Natalia; Iwan, Agnieszka; Marzec, Monika
Abstract : We have shown that admixtures of 5CB and SWCN accelerate the degradation of l, d -PLA in the composite layer due to hydrophilic/hydrophobic interface in the layer and act as plasticizers. The mechanism of the degradation process is also discussed. Abstract : The aim of the study was to investigate the influence of the environment's pH on the degradation of the layers of the ternary composite l, d -PLA : 5CB : SWCN (10 : 1 : 0.5, w/w/w), where l, d -PLA (poly(lactic acid)) is a biodegradable polymer, 5CB is a well-known liquid crystal (4′-pentyl-4-biphenylcarbonitrile), and SWCN are single-walled carbon nanotubes. For this purpose, the samples were stored in air, distilled water, and solutions of 0.1 M NaOH and 0.1 M HCl, for up to 62 days. Using differential scanning calorimetry, atomic force microscopy, and infra-red spectroscopy methods it was observed that for both neat l, d -PLA and composite layers there was a poor degradation process after the storage under standard air conditions, distilled water, and 0.1 M HCl solution, while the erosion of the surface layer kept in 0.1 M NaOH solution was revealed just after 6 days. The longer storage in 0.1 M NaOH solution resulted in complete degradation of the l, d -PLA polymer layer, while the composite layer survived for up to 62 days. The solubilization of the polymeric l, d -PLA matrix in the composite after 62 days was so severe that it resulted in the vanishing of thermal effects on the DSC curve except for one that was probably connected with the glass transition of the residual quantity of the polymer that remained in the layer or the isotropisation of 5CB. As a result, we have shown that admixtures of 5CB and SWCN accelerate the degradation of l, d -PLA in the composite layer due to the hydrophilic/hydrophobic interface in the layer and act as plasticizers. The mechanism of the degradation process is also discussed.